Colonic Metastases from a Luminal A Type Invasive Ductal Carcinoma Breast: A Rare Case Report - Sehrawat, Amit; Kotwal, Sumedha Ahal; Gupta, Deni (Indian Journal of Medical and Paediatric Oncology, 2020)
Metastatic carcinoma breast involving hepatobiliary system and peritoneum is a common and well-described entity. However, colonic luminal involvement by breast metastases is rare and its early recognition is important for accurate management planning. We report a case of an elderly woman with luminal A type invasive ductal carcinoma (IDC) breast, initially controlled/stabilized on hormonal treatment and later progressed to involve colon presenting with intestinal obstructive symptoms. Lobular carcinoma breast which constitutes around 10% of breast cancers is more likely to have gastrointestinal tract (GIT) involvement. On the other hand, GIT metastasis from IDC breast is quite rare. Given the progressively increasing survival with current and forthcoming novel treatment modalities, it is very important to recognize and understand unusual presentation of metastatic breast cancer, such as colonic metastasis, for timely treatment planning and implementation.
Keywords: Carcinoma breast; colonic metastases; invasive ductal carcinoma; unusual metastasis